Serum antibody response to Moraxella catarrhalis proteins in stringently defined otitis prone children. Issue 32 (26th July 2019) - Ren, Dabin; Almudevar, Anthony L.; Murphy, Timothy F.; Lafontaine, Eric R.; Campagnari, Anthony A.; Luke-Marshall, Nicole; Pichichero, Michael E.
Abstract: Background: Moraxella catarrhalis ( Mcat ) is a frequent pathogen of acute otitis media (AOM) in young children. Here we prospectively assessed naturally-induced serum antibodies to four Mcat vaccine candidate proteins in stringently defined otitis prone (sOP) and non-otitis prone (NOP) children age 6–36 months old following nasopharyngeal (NP) colonization, at onset of AOM and convalescence from AOM. Methods: Serum IgG and IgM antibody against recombinant Mcat proteins, oligopeptide permease A (OppA), outer membrane protein (OMP) CD, hemagglutinin (Hag), and PilA clade 2 (PilA2), were quantitated by ELISA. Results: During NP colonization by Mcat all four antigens were immunogenic in both sOP and NOP children. However, sOP children had lower antibody responses than NOP children across age 6–36 months, similar to our findings for protein vaccine candidates of Streptococcus pneumoniae ( Spn ) and Nontypeable Haemophilus influenzae (NTHi). sOP children displayed a later and lower peak of antibody rise than NOP children for all four antigens during NP colonization of Mcat . The age-dependent increase of antibody ranked as OppA > Hag5-9 > OMP CD > PilA2 in both sOP and NOP children. Lower serum antibody levels to the Mcat antigens were measured in sOP compared to NOP children at the onset of AOM. We did not find a consistent significant increase of antibody at the convalescence phase after an AOM event. Conclusions: sOP children is a highly vulnerable population that mount lower serum antibody responses to Mcat candidate vaccine proteins compared to NOP children during asymptomatic NP carriage and at onset of AOM.